2019
DOI: 10.59096/osir.v12i1.263017
|View full text |Cite
|
Sign up to set email alerts
|

An Enterovirus Outbreak Associated with Probable Rhombencephalitis in a Nursery, Tak Province, Thailand, 2017

Abstract: On 4 Sep 2017, the Bureau of Epidemiology received a notification from Tak Provincial Health Office on an outbreak of hand, foot and mouth disease (HFMD) at a nursery following one death at the provincial hospital. An investigation was carried out to confirm the diagnosis and identify source of infection. Active case finding was performed in the nursery, index case’s house and community. Medical records were reviewed, and children, teachers and household members of the index case were interviewed. Confirmed ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…In addition to aseptic meningitis, coxsackieviruses have been associated with encephalitis (inflammation of the brain parenchyma), meningoencephalitis (severe inflammatory process of the brain parenchyma and meninges), and rhombencephalitis (brainstem encephalitis and cerebellitis). Indeed, numerous studies have revealed different CV types as causative agents of these inflammatory processes, such as CVA2, CVA3, CVA4, CVA5, CVA6, CVA7, CVA9, CVA10, CVA16, CVA21, CVB1-B5 (encephalitis) ( Moore, 1982 ; Zhang et al, 2013 ; Nagai et al, 2021 ; Fowlkes et al, 2008 ; Chen et al, 2020 ; Kriger et al, 2023 ), CVA6, CVA9, CVA10, CVA11, CVA16, CVB2-B5 (meningoencephalitis) ( Schoub et al, 1985 ; Cree et al, 2003 ; I.P.D Sousa et al, 2021 ; Dorta-Contreras et al, 2008 ; Li et al, 2014 ; McKinney et al, 1987 ; Wakamoto et al, 2000 ) and CVA9, CVA16, CVB2, and CVB4 (rhombencephalitis) ( Table 1 ) ( Kriger et al, 2023 ; Goto et al, 2009 ; Pisitpayat et al, 2019 ; Huang et al, 2013 ), including fatal cases. The most common CV types associated with these conditions are CVA9, CVB2, CVB3, and CVB5 ( Jmii et al, 2021 ; Cherry and Krogstad, 2009 ; Suresh et al, 2020 ; Zhang et al, 2013 ).…”
Section: Cv-associated Infectionsmentioning
confidence: 99%
“…In addition to aseptic meningitis, coxsackieviruses have been associated with encephalitis (inflammation of the brain parenchyma), meningoencephalitis (severe inflammatory process of the brain parenchyma and meninges), and rhombencephalitis (brainstem encephalitis and cerebellitis). Indeed, numerous studies have revealed different CV types as causative agents of these inflammatory processes, such as CVA2, CVA3, CVA4, CVA5, CVA6, CVA7, CVA9, CVA10, CVA16, CVA21, CVB1-B5 (encephalitis) ( Moore, 1982 ; Zhang et al, 2013 ; Nagai et al, 2021 ; Fowlkes et al, 2008 ; Chen et al, 2020 ; Kriger et al, 2023 ), CVA6, CVA9, CVA10, CVA11, CVA16, CVB2-B5 (meningoencephalitis) ( Schoub et al, 1985 ; Cree et al, 2003 ; I.P.D Sousa et al, 2021 ; Dorta-Contreras et al, 2008 ; Li et al, 2014 ; McKinney et al, 1987 ; Wakamoto et al, 2000 ) and CVA9, CVA16, CVB2, and CVB4 (rhombencephalitis) ( Table 1 ) ( Kriger et al, 2023 ; Goto et al, 2009 ; Pisitpayat et al, 2019 ; Huang et al, 2013 ), including fatal cases. The most common CV types associated with these conditions are CVA9, CVB2, CVB3, and CVB5 ( Jmii et al, 2021 ; Cherry and Krogstad, 2009 ; Suresh et al, 2020 ; Zhang et al, 2013 ).…”
Section: Cv-associated Infectionsmentioning
confidence: 99%